1995
DOI: 10.1111/j.1365-3083.1995.tb03685.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotypic and Functional Characteristics of Haemopoietic Cells from Human Cord Blood

Abstract: Cord blood (CB) as a new source for bone marrow transplantation represents advantageous features concerning stem cell and leucocyte compartments and function. We attempted to get more information about the phenotypes and function of CB cells by investigating their cell surface markers and also the production of IL-2, IFN-gamma and IL-6 by mitogen and alloantigen stimulation. The CB cells were characterized by a low proportion of CD3+ T cells, CD4+ T subpopulation, activated T cells and CD3+CD16/CD56+ cytotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
3

Year Published

1997
1997
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 15 publications
2
22
0
3
Order By: Relevance
“…29 These data together give recipients, which indicated early recovery and supernormal percentage of IgM + B cells for the whole follow-up period. 13 support to the hypothesis that the reduction of post-BMT complications after DBM preconditioning could be due, in A sparing effect of DBM on certain specific immune responses was demonstrated earlier in murine studies, too. 15,20 Namely, addition to the relatively mild B cell toxicity, to a relative lack of long-term thymus toxicity.…”
Section: Start Subtotalsupporting
confidence: 76%
See 1 more Smart Citation
“…29 These data together give recipients, which indicated early recovery and supernormal percentage of IgM + B cells for the whole follow-up period. 13 support to the hypothesis that the reduction of post-BMT complications after DBM preconditioning could be due, in A sparing effect of DBM on certain specific immune responses was demonstrated earlier in murine studies, too. 15,20 Namely, addition to the relatively mild B cell toxicity, to a relative lack of long-term thymus toxicity.…”
Section: Start Subtotalsupporting
confidence: 76%
“…13 In brief, the spleen was homogenized in Medium It is known that the rise of GVHD along with the various 199, and 5 × 10 5 cells in 50 l volume (in the wells of 96-bacterial and/or fungal infections are due to the myelowell U-bottom plates) were stained with 1:100 diluted rat ablation-induced immunosuppression that endures over a monoclonal anti-Thy-1.2 (30-H12) antibodies. Following long time after BMT.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19] These data indicate that using only one-color CD34 analysis may not provide sufficient information, 12,15 but sensitive detection and enumeration of CD34 + cells is required. 12,13,15 The widespread use of CD34 expression as a measure of the transplant potential of hematopoietic tissue also means that it is important to establish any antibody-or tissue-related differences in levels of expression. 14 As a result of the different levels of detection by different MoAbs, the apparent number of CD34 + cells vary by approximately six-fold.…”
Section: Quantity and Quality Of Immature Hematopoietic Stem Cells Frmentioning
confidence: 99%
“…It has been demonstrated that committed hematopoietic progenitor cells are at least as numerous in cord blood as in normal BM. 13,15,16 Cord blood cells can be extensively expanded in suspension culture with different combinations of cytokines, 20 as well as in NOD/SCID mice 17 and other murine model in vivo. 21 Thus, immature hematopoietic stem cells and progenitor cells appear to be of good quality in cord blood.…”
Section: Quantity and Quality Of Immature Hematopoietic Stem Cells Frmentioning
confidence: 99%
“…5 Much research has been conducted to clarify the characteristics of UCB lymphocytes. In summary, it has been reported that UCB has fewer CD3-positive T lymphocytes, [6][7][8][9][10] among which the majority express the naive, nonprimed CD45RA marker, and express fewer IL-2 receptor Correspondence: Dr M Hagihara, Department of Hematology and Rheumatology, Tokai University School of Medicine, Bohseidai, Isehara, Kanagawa 259-1193, Japan Received 29 April 1999; accepted 18 July 1999 molecules than adult PBL. 8 However, there is controversy about the immunoreactivity of UCB lymphocytes against allo-antigens.…”
mentioning
confidence: 99%